Volunteer tourism in the global south : giving back in neoliberal times - Vrasti, Wanda (Milton Park, Abingdon, Oxon ; New York : Routledge, 2013)
"This work explores the increasingly popular phenomenon of volunteer tourism in the Global South, paying particular attention to the governmental rationalities and socio-economic conditions that valorize it as a noble and necessary cultural practice"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Volunteer tourism -- Developing countries; Volunteer tourism -- Economic aspects -- Developing countries; Volunteer tourism -- Social aspects -- Developing countries; Volunteer tourism -- Government policy -- Developing countries; Electronic books